Sistem Pengendali Otomatis Debit Air Pada Simulasi Bendungan Menggunakan Mikrokontroler Atmega 32 Dan Komunikasi Serial - Zulfachmi; Wanhendra; Danandjaya Saputra (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2020)
Dam is a construction that is built to restrain rate of water into a reservoir, lake, or recreation area. Often dams are also used to drain water to a hydroelectric power plant. Most dams also have a section called the water gate to remove unwanted water gradually or continuously. Based on the existing problems, the author analyzes and designs a new system that anticipates weaknesses in the running system without causing new problems. The automatic control system for water discharge in the dam simulation uses the ATMEGA 32 microcontroller and the serial communication that the author proposes has answered the problems that arise. The automatic control system for water discharge in the dam simulation using the ATMEGA 32 microcontroller and serial communication can give good results in providing water level data in the aquarium container tested. The software used as a tool in this research is Borland Delphi7 and Arduino and the methodology used for the development of this application is the Spiral method. The results of the development of this system are expected to make it easier for the government to fix waterways.